Forest-type mapping from airborne polarimetric SAR data - Seeni Mohd., Mohd. Ibrahim; Siou, Eric Chee Yoong; Yusoff, Safiah @ yusmah (2001)
Mapping of forest types from satellite data is quite difficult due to poor spatial resolution. This study evaluates the use of polarimetric Airborne Synthetic Aperture Radar (AIRSAR) data to assess forest type distribution within the area of Endau Rompin Pahang, Malaysia. Radar backscattering coefficients were evaluated on the L and P band for HH, HV and VV polarization. Statistical evaluation was carried out to determine the Coffiencent ofr Variance (COV) and the best combination was determined by calculating the correlation among the bands.